1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<610::aid-immu610>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer with IL-4 and IL-13 improves survival in lethal endotoxemia in the mouse and ameliorates peritoneal macrophages immune competence

Abstract: Systemic anti-cytokine therapies have been unsuccessful in preventing mortality from gram-negative bacteremia in humans partly because of the failure to neutralize pro-inflammatory cytokines at sites of exaggerated production. In an attempt to deliver anti-inflammatory cytokines to organs directly, gene transfer was employed. Thirty-six BALB/c mice were injected intraperitoneally with cationic liposomes containing plasmids encoding the human interleukin-4 (hIL-4) or IL-13 gene. Both, hIL-4 and hIL-13 mRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…This hypothesis, however, is only a possible mechanism because there are no data to support systemic anergy in the present study. IL-10 may also be involved in immune depression associated with hemorrhage [26,27]. B-cells, helper T-cells, monocytes, and macrophages might be the major sources of IL-10 [28].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis, however, is only a possible mechanism because there are no data to support systemic anergy in the present study. IL-10 may also be involved in immune depression associated with hemorrhage [26,27]. B-cells, helper T-cells, monocytes, and macrophages might be the major sources of IL-10 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Direct experiments in the BIAcore system have revealed that normally glycosylated mouse full-length IL-4 directly binds to human IL-4R␣ [121]. Moreover, several previous reports have shown that human full-length IL-4 is active in mouse or rat in vivo in a fashion similar to that of rodent full-length IL-4 [122,123]. We found that human full-length IL-4 is active in mice in vivo [29], but this activity is only partially similar to that of mouse full-length IL-4 [28].…”
Section: Receptor Use By and Cross-species Activities Of Il-4␦2mentioning
confidence: 98%
“…The role of endogenous IL-4 in controlling the host septic response is unclear, although low, but significant levels of IL-4 have been detected in the serum of rabbits challenged with endotoxin and in patients with sepsis [8,117]. However, the systemic overexpression of human IL-4 in mice using cationic liposome-mediated gene transfer has recently been shown to be protective in a murine LPS/D-galactosamine-induced shock model, as survival in mice expressing the IL-4 transgene was 83%, as compared to only 20% survival in control animals [118]. This protective effect was associated with an 80% reduction in serum TNF-α levels.…”
Section: Il-4 In the Pathogenesis Of Sepsis Syndromementioning
confidence: 99%
“…Similarly, overexpression of human IL-13 by cationic liposome-mediated gene transfer in LPS/Dgalactosamine-treated mice resulted in a substantial increase in survival. In fact, IL-13 overexpression attenuated endotoxin-induced TNF-α production to a greater degree than did the systemic overexpression of human IL-4 [118]. The role(s) of IL-13 in inflammatory arthritis and IBD have not yet been defined.…”
Section: Il-4 In the Pathogenesis Of Inflammatory Arthritismentioning
confidence: 99%